SENTIMENT ANALYSIS ON HALAL CERTIFICATION - Bashir Ammar Hakim Hakim; Anisa Syahidah Mujahidah; Aam Slamet Rusydiana (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2022)
Halal Certificate is a halal guarantee certificate for a product issued by an institution, be it a private institution or a government agency. There are pros and cons among the public and researchers regarding the existence of Halal certification. Therefore, this research was conducted to examine halal certification within the scope of the economy in terms of the opinions of Twitter social media users. The method used in this research is a qualitative approach with descriptive statistics from literature studies with the theme of halal certification. The data used in this study are 13,824 tweets related to Halal Certification. To classify tweets, a Python library called VADER (Valence Aware Dictionary and Sentiment Reasoner) is used. VADER (Valence Aware Dictionary and Sentiment Reasoner) is a lexicon and rule-based sentiment analysis tool adapted to social media sentiment but also works on texts from other domains. The results of the sentiment analysis show that there is a tendency for positive perceptions of Halal Certification in the opinion of Twitter users, with positive sentiment of 41.8%, neutral sentiment of 30.8% and negative sentiment of 27.4%. This diversity of sentiment results is obtained because of the pros and cons of the existence of Halal Certification. The benefit of this research is for literature material and considerations related to Halal Certification. As well as efforts to identify threats, negative perceptions, and lack of Halal certification. In addition, to find out positive perceptions, advantages and benefits of Halal Certification.